Let's solve the equation step by step:
Given equation: \[ 2(x - 3) + 21 = -3 \]
Step 1: Distribute
We need to distribute the 2 across the terms inside the parentheses. \[ 2(x) - 2(3) + 21 = -3 \] This simplifies to: \[ 2x - 6 + 21 = -3 \]
Step 2: Combine like terms
Now, combine like terms on the left side: \[ 2x + ( -6 + 21 ) = -3 \] This simplifies to: \[ 2x + 15 = -3 \]
Step 3: Use the Subtraction Property of Equality
To isolate the term with x, we subtract 15 from both sides: \[ 2x + 15 - 15 = -3 - 15 \] This results in: \[ 2x = -18 \]
Step 4: Use the Division Property of Equality
Next, we divide both sides by 2 to solve for x: \[ \frac{2x}{2} = \frac{-18}{2} \] This simplifies to: \[ x = -9 \]
Final Answer
The solution to the equation is: \[ x = -9 \]